Microwave-Assisted Synthesis of Cross-Linked Co-poly(itaconic anhydride-methyl methacrylate): The Effects of the Molar Ratio and Cross-Linking Agent on the Thermal Stability - Ali Aldalbahi; Mostafizur Rahaman; Ayman El-Faham (International Journal of Polymer Science)
In the present work, a new series of cross-linked copolymers based on itaconic anhydride and methyl methacrylate were prepared employing free radical copolymerization in the presence of azobisisobutyronitrile as an initiator and 2-butanone as a solvent under microwave irradiation. The copolymers containing itaconic anhydride (ITA) and methyl methacrylate (MMA) were chosen due to the formation of long-term stable anhydride moieties, which might be useful to attach enzymes covalently with numerous applications in water treatment. The copolymerization process was carried out in the presence of two types of cross-linking agent, namely, ethylene dimethacrylate (EDMA) and divinylbenzene (DVB) in a range of 0-20% (w/w) to explore their effect on the thermal and stiffness properties of the obtained cross-linked copolymers. Increasing the ratio of the cross-linking agent, the copolymers prefer to precipitate rather than form a gel during the polymerization process. While using ethylene dimethacrylate as a cross-linking agent, the copolymers change from porous to stiffness structures depending on the molar ratio of the monomers used during the polymerization. On the other hand, using divinylbenzene as a cross-linking agent, the stiffness structure was obtained in all cases and there is no effect observed for the monomer’s ratio or the percentage of cross-linking agent on the morphology of the prepared copolymers.